Impact of sensitization workshop on knowledge and awareness of hospital-acquired infection among nurses of a teaching hospital in India (South East Asia Journal of Public Health, 2013)
Hospital-acquired infection (HAI) in healthcare settings is the most frequent adverse event in healthcare delivery worldwide. Hundreds of millions of patients are affected by HAI worldwide each year, leading to significant patient mortality rates and financial losses for health systems. We evaluated the impact of a sensitization workshop on knowledge and awareness of HAI among nurses in a medical college hospital in rural area of Ahmednagar district, India from March 2010 to August 2010. One hundred staff nurses, who had more than one year of experience, had attended the workshops on HAI. Pre- and post-test data was collected by a questionnaire. A significant increase in number of nurses having knowledge regarding commonly occurring HAI and routes of transmission , barrier nursing and hygienic hand washing techniques, hospital waste management (its importance and color coding), and the im-portance of an infection control team was observed after the workshop. Education and training of healthcare workers about standard infection control can reduce the extent of risks of HAI. Nurses have a critical role to play in preven-tion measures and infection control and they should have the opportunity for continuous professional development. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15960 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 77-79